Gut microbiota analysis of healthy and sacbrood virus-infected Apis mellifera reveals potential probiotic bacteria for honeybee health and disease resistance - Quyen, Dong Van; Thuy Duong, Bui Thi; Lanh, Pham Thi; Thu, Ha Thi (Academia Journal of Biology, 2025)
This study aimed to determine the gut microbiota composition of adult Apis mellifera honeybees from bee farms in Bac Giang province, including both healthy colonies and those infected with Sacbrood virus (SBV). The gut microbiota of healthy and SBV-infected bees was assessed using next-generation sequencing (NGS) of the V3-V4 region in the 16S rRNA gene on the Illumina MiSeq system. As a result, NGS analysis identified 1,659 operational taxonomic units (OTUs) with a coverage of 99% and an average read length of 430 bp. The results revealed that SBV-infected bees harbored four microbial phyla: Proteobacteria (48.44%), Firmicutes (38.65%), Actinobacteria (1.57%), and Bacteria_uc (10.95%). In contrast, the healthy bee group consisted of three phyla: Proteobacteria (40.61%), Firmicutes (45.55%), and Bacteria_uc (13.37%). The species composition analysis showed that both healthy and SBV-infected bees shared common core bacterial species. However, Bifidobacterium_uc and Commensalibacter AY370188_s were more prevalent in SBV-infected bees and significantly reduced in healthy bees. Conversely, Fructobacillus fructosus and Lactobacillus kunkeei were found exclusively in healthy bees. These lactic acid bacteria (LAB) have been shown to inhibit the growth of pathogenic bacteria. Our findings provide a valuable scientific foundation for developing biological products to improve honeybee health and disease resistance.